Virtual reality : a broader perspective of human-computer synergy - Creel, Josh, editor (New Jersey, N.J. : Clanrye International, 2015)
Virtual reality has been a major influence in the development of information organization and management. Furthermore, it has also changed the process of designing information systems to make them more suitable for required applications. This book covers a wide range of applications of virtual reality and developments occurring in this field. The book discusses the applications of virtual reality in varied fields such as robot technology, industry and construction, and multimedia technology. This book will be beneficial for readers interested in learning more about the field of virtual reality.